2020
DOI: 10.18488/journal.aefr.2020.1011.1309.1320
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Economic Linkages among Small and Medium Enterprises, Economic Growth, and Employees in Malaysia

Abstract: This paper investigates the linkages among economic growth, small and medium enterprises (SMEs) and employees in Malaysia. It uses the total number of SME employees as a third variable to be associated with economic and SME growth using a panel dataset covering the period from 1998 to 2017. There are five main economic sectors in Malaysia: agriculture, construction, mining, manufacturing and services. The aim of the paper is to provide a better understanding of the relationship between SMEs, economic growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
2
0
1
Order By: Relevance
“…Again, the research also concluded that firm size was significantly correlated with access to credit. This collaborates the work of Nguyen & Ramachandran, (2006); Musamali and Tarus, (2013) reported earlier in the previous subsections.…”
Section: Empirical Evidence Of the Length Of Time In Operation And Ac...supporting
confidence: 92%
See 1 more Smart Citation
“…Again, the research also concluded that firm size was significantly correlated with access to credit. This collaborates the work of Nguyen & Ramachandran, (2006); Musamali and Tarus, (2013) reported earlier in the previous subsections.…”
Section: Empirical Evidence Of the Length Of Time In Operation And Ac...supporting
confidence: 92%
“…Logistic regression and ordinary least squares were used to analyse and estimate the data, respectively. The results showed that firm size is positively associated with accessibility to bank loans Musamali and Tarus (2013). conducted empirical evidence to analyse the effect of firm characteristics on SME firms on access to credit in Kenya using primary data collected from 103 SME businesses using questionnaires.…”
mentioning
confidence: 99%
“…Thus, the collateral requirement can also help to weed out rogues from honest borrowers, leaving only those bona-fide applicants who fully intend to repay the loan. Martin and Daniel (2013) found out that firm age plays a critical role in firms' access to finance. More specifically, firms that are older were found to have more access to finance.…”
Section: • Firm Level Characteristicsmentioning
confidence: 99%
“…Petersen and Rajan (1994) in their estimation argued that as firms grow, they develop a greater ability to enlarge the circle of banks from which they can borrow. Martin and Daniel (2013) suggested that the reason for the effect of the size of the business on the ability to access finance is that larger firms are likely to have collaterals that act as a security in securing finances. Abor (2007) in Ghana examined the effect of industry classification on the capital structure of Ghanaian SMEs.…”
Section: • Firm Level Characteristicsmentioning
confidence: 99%
“…Di negara berkembang, UKM berkontribusi dalam banyak hal, seperti: pengentasan kemiskinan dengan membantu masyarakat meningkatkan pendapatannya melalui kesempatan kerja yang dihasilkan oleh sektor UKM yang lebih luas, memperluas kegiatan ekonomi di daerah pedesaan dan menyediakan berbagai sumber daya untuk membantu pertumbuhan ekonomi suatu negara. Selain menyediakan dukungan dan memasok perusahaan besar, UKM juga bekerja untuk merangsang keterampilan kewirausahaan di kalangan masyarakat, dan bertindak sebagai agen dalam pengembangan perusahaan domestik menjadi perusahaan besar (Adan et al, 2020). Selain itu, UKM juga berkontribusi pada anggaran negara melalui pembayaran pajak (Pham et al, 2021).…”
Section: Pendahuluanunclassified